Limitations of the Indonesian Pediatric Tuberculosis Scoring System in the context of child contact investigation - Rina Triasih; Stephen M. Graham (Paediatrica Indonesiana, 2011)
tuberculosis (TB) was developed to address the problem of overdiagnosis. The implementation of this scoring system in children who have household TB contacts has not been evaluated.Objective To evaluate the performance of the Indonesian pediatric tuberculosis scoring system in the context of contact investigation.Methods A cross-sectional study was conducted in the Yogyakarta municipality, between August 2010 and March 2011. Subjects were children under the age of 15 years, living in the same house with an adult who had pulmonary TB. Subjects underwent history taking, physical examinations, tuberculin skin tests (TST) and chest X-rays. Sputum smear was performed in symptomatic children. We compared outcomes of the Indonesian pediatric TB scoring system to that of rigorous clinical assessment.Results A total of 146 eligible children of 82 source cases were recruited into the study. Sixty-eight (47%) children had positive TST tuberculin skin tests. Using the scoring system, 47% of the subjects were diagnosed to have TB disease, while only 10% were diagnosed with TB using rigorous clinical assessment. With rigorous clinical assessment, 40% of the subjects were diagnosed as having latent TB infection (LTBI), while none of the subjects were diagnosed as LTBI using the scoring system.Conclusion The use of the Indonesian pediatric TB scoring system in children with household TB contact may lead to overdiagnosis of TB disease.